MARY BARTON. - GASKELL, ELIZABETH (OPEN ROAD MEDIA, 2017)
A tale of love, class, and murder during the era of the trade-union movement in nineteenth-century England, from the author of North and South. In Manchester, long-suffering John Barton and his daughter, Mary, both want a better future for each other. John toils away with the trades' union for better wages for his fellow workers in the textile mill, while Mary must consider whom she will marry. She decides to leave the working-class Jem Wilson, hoping instead to wed Harry Carson, the wealthy mill owner's son. But when Harry is shot down in the street, Jem becomes the prime suspect'and learning the truth may yield a future Mary cannot bear. A portrait of the working class's struggles during the Victorian era, Mary Barton was Elizabeth Gaskell's first novel. She went on to write classics such as Wives and Daughters and was the creator of the town of Cranford, the setting for several BBC series.